Development of a Practical Model to Predict Conversion to Total Hip Arthroplasty Following Non-Vascularized Bone Grafting - Gao, Shihua; Mo, Liang; Cai, Kaishen; He, Wei; Li, Ziqi (Frontiers in Surgery, 2022)
Objective: To identify risk factors of failure after Non-Vascularized Bone Grafting (NVBG) in osteonecrosis patients, establish and validate a nomogram predictive model of hip survival after NVBG. Methods: Data on ONFH patients undergoing NVBG at our institution between 2010 and 2017 were retrospectively collected. Preoperative risk factors potentially associated with failure after NVBG were assessed by univariate Cox regression analyses. A predictive nomogram was developed based on multivariate Cox regression model. The performance of the nomogram model was evaluated by C statistic. Subjects were stratified according to total points calculated from the nomogram and Kaplan-Meier curves were plotted to further evaluate the discrimination of the model. The model was also internally validated through calibration curves. Results: The overall 2-year and 5-year hip survival percentages were 91.8% and 84.6%, respectively. Age, etiology, Association Research Circulation Osseous stage and range of necrotic lesion were independent risk factors of failure after NVBG. The C statistic of the nomogram model established with these predictors was 0.77 and Kaplan-Meier curves of the tertiles showed satisfactory discrimination of the model. Internal validation by calibration curves indicated favorable consistency between actual and predicted hip survival rate. Conclusion: This predictive model may be a practical tool for patient selection of NVBG. However, future studies are still needed to externally validate this model.